Synthesis, Characterization and Molecular Docking of Furaldehyde-Substituted Benzimidazoles via Sodium Metabisulfite-Catalyzed Oxidative Cyclocondensation in DMF - Rani, Rekha; K, Saravanan (Journal of Neonatal Surgery, 2025)
A series of novel furaldehyde-substituted benzimidazole derivatives was synthesized via a sodium metabisulfite-catalyzed oxidative cyclocondensation reaction in dimethylformamide (DMF) [6]. This method offered a convenient and efficient route to construct the benzimidazole core under mild reaction conditions, yielding the desired compounds in good to excellent yields [3,6]. The use of furaldehyde, a renewable bio-based aldehyde, contributes to the green chemistry aspects of this synthesis [5]. The synthesized compounds were structurally characterized using Fourier-transform infrared spectroscopy (FTIR), proton nuclear magnetic resonance (¹H-NMR), and mass spectrometry (MS), confirming the formation of the expected benzimidazole framework [1,4]. This approach presents a practical and environmentally benign synthetic pathway for generating structurally diverse benzimidazole analogs for future pharmacological studies